Learning How to Be a Student: An Overview of Instructional Practices Targeting School Readiness Skills for Preschoolers With Autism Spectrum Disorder. (January 2015) - Fleury, Veronica P.; Thompson, Julie L.; Wong, Connie
Due to difficulties associated with autism spectrum disorder (ASD), many children with ASD will require additional support to actively participate in classroom activities. Therefore, it is important that professionals who work with young children with ASD know what skills to teach and how to teach them. Using the recent evidence-based practice review conducted by the National Professional Development Center on ASD, we have identified studies that targeted school readiness behaviors which can have implications for academic skill development. In this article, we evaluate (a) the types of skills that have been taught to preschool children with ASD, (b) the strategies used to teach specific skills, and (c) other descriptive information, such as who delivered the intervention and the setting in which the intervention took place. We conclude by offering suggestions for future research and considerations for professional development.